USE OF FOODSTUFFS WITH PRO-AND PREBIOTIC ACTIONS IN INFANT FOOD - K.S. Ladodo; T.E. Borovik; V.A. Skvortsova ("Paediatrician" Publishers LLC, 2006)
The article deals with the data about opportunity to enrich the modern infant foodstuffs with pro and prebiotics. The authors name the contents of the foodstuffs with pro and prebiotic properties, findings of the multicentric research according to the estimate of their clinical efficiency among healthy and ill infants. They show the safety and high efficiency of the use of the given healthful and dietary foodstuffs.Key words: infant food, foodstuffs, probiotics, prebiotics, bifidus bacteria, lactic acid bacilli, oligosaccharides, lactulose, inulin.